组合式双压电混合燃料喷射装置 (2018)
本发明的目的在于提供组合式双压电混合燃料喷射装置，包括双压电控制部分、喷嘴部分、进气通道、进油油道等。本发明将燃气喷嘴和燃油喷嘴组合在个喷射装置外壳内，两喷嘴都采用压电元件控制针阀的运动，针阀升程可调，燃料喷射量及燃料喷射率控制精度高；两喷嘴由两针阀分别控制燃油和燃气的喷射，燃料喷射灵活性高，能够实现纯燃油工作模式和双燃料工作模式；燃气喷嘴的针阀腔和针阀偶件处的燃油为同种油，油压相等，避免了针阀偶件处的燃油静态泄漏；燃气喷嘴用燃油密封燃气，有利于避免燃气通过针阀偶件泄漏，提高了燃气喷射压力和喷射速率，改善了发动机的动力性和燃料经济性。 The invention aims at providing a combined dual piezoelectric mixed fuel injection device. The device comprises a dual piezoelectric control part, a nozzle part, a fuel gas inlet channel, a fuel oil inlet channel and the like. A fuel gas nozzle and a fuel oil nozzle are combined in an injection device shell, the two nozzles each adopts a piezoelectric element to control motion of a corresponding needle valve, the needle valve lift is adjustable, and the control accuracy of the fuel oil injection amount and fuel injection rate is high; two needle valves are adopted by the nozzles to control fuel oil injection and fuel gas injection respectively, the fuel injection flexibility is high, and a pure fuel working mode and a dual-fuel working mode ca